2018
DOI: 10.1007/s00604-018-2999-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric determination of doxycycline based on the use of carbon quantum dots incorporated into a molecularly imprinted polymer

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 38 publications
(41 reference statements)
0
22
0
Order By: Relevance
“…Variation of percentage removal of DOH with contact time at a different initial concentration range from (50-125 mg. L -1 ), times in the range of (15 to 120) minutes, 0.1gm Al 2 O 3 and temperature 37.5°C [2]. From Table 2, it was observed that with a rise in the initial DOH concentration from 50 to 125 mg. L -1 , the capacity of DOH adsorption increases, while the removal percentage was larger for low initial DOH concentration, this can be explained by the accessibility of vacant binding sites on the adsorbent.…”
Section: Adsorption Studies 1-effect Of Initial Concentration and Conmentioning
confidence: 90%
See 1 more Smart Citation
“…Variation of percentage removal of DOH with contact time at a different initial concentration range from (50-125 mg. L -1 ), times in the range of (15 to 120) minutes, 0.1gm Al 2 O 3 and temperature 37.5°C [2]. From Table 2, it was observed that with a rise in the initial DOH concentration from 50 to 125 mg. L -1 , the capacity of DOH adsorption increases, while the removal percentage was larger for low initial DOH concentration, this can be explained by the accessibility of vacant binding sites on the adsorbent.…”
Section: Adsorption Studies 1-effect Of Initial Concentration and Conmentioning
confidence: 90%
“…Antibiotics are among the most important pharmaceutical compounds found in the aquatic environment. They have been discovered in different aquatic environments such as groundwater, agricultural drainage water and drinking water [1][2][3]. Animal waste used as fertilizer is a major source of water pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic Quenching Mechanism of CDs: If the collisions between CD and quencher result in the ground state return of fluoro phore due to energy transfer, the effect is said to be dynamic quenching. [49,85] The criteria for dynamic quenching are exactly the opposite of static quenching. There will be a change in the lifetime of CD in the absence and presence of quencher and the quenching constant increases with an increase in tempera ture.…”
Section: Quenching Mechanismsmentioning
confidence: 99%
“…The co-doping of N and S increases the number of active sites on the CDs surface, thus enhancing its luminescence performance [ 36 ]. Nitrogen-doped carbon quantum dots (NCQDs), a fluorescent probe, were successfully applied to the determination of doxycycline [ 37 ]. Pathak et al prepared co-doped carbon dots with nitrogen and sulfur (NSCDs) as well, which were synthesized from thiourea and tris–acetate-ethylenediamine buffer by microwave hydrothermal method.…”
Section: Synthesis Of Fluorescent Nanomaterialsmentioning
confidence: 99%